Feedback Optimization Table- printable double sided - Cunningham, Kelly (University of Virginia, 2022)
A printable double sided handout outlining how to optimize feedback and use the awareness scale. One side includes a monster bug scenario. Scale concept is based on work by Purdue OWL's Faculty guide to working with graduate writers
Original submission date: 2022-10-10T18:11:26Z
Keywords: Feedback; Feedback Optimization; Feedback Stages; Feedback Table; Graduate Students; Graduate Writing Lab; GWL